Remimazolam Tosylate Combined with Low-Dose Propofol Improves Sedation and Safety in Hysteroscopy - Zhang F; Chang H; Qing W; Yu R; Liao Q; Tong J (Dove Medical Press, 2022)
Fan Zhang, Huan Chang, Wenxiang Qing, Rili Yu, Qin Liao, Jianbin Tong Department of Anesthesiology, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, People's Republic of ChinaCorrespondence: Jianbin Tong; Qin Liao, Department of Anesthesiology, The Third Xiangya Hospital, Central South University, No. 138 Tongzipo Road, Changsha, Hunan, 410013, People's Republic of China, Email jianbintong@csu.edu.cn; xy3yyliaoqin@sina.comBackground: Propofol is widely used for sedation of hysteroscopy. It can cause injection pain, respiratory depression, and hypotension. Remimazolam is a novel ultra-short-acting benzodiazepine. Clinical practice has found that the use of remimazolam alone often leads to body movement during hysteroscopy, which decreases the safety and comfort. Here this study is to investigate whether remimazolam combined with low-dose propofol can improve the sedation effect and safety of hysteroscopy.Patients and Methods: In this prospective, randomized, parallel-controlled trial, women (18 to 60 years) undergoing hysteroscopy were randomly assigned to receive propofol (Group P), remimazolam tosylate (Group R), or remimazolam tosylate plus propofol (Group RP). Intraoperative sedation depth was kept at the bispectral index (BIS) value of 40- 60. 6 μg/kg alfentanil was used for analgesic before sedation. Intraoperative low pulse oxygen saturation (SpO2), body movement, injection pain, mean arterial pressure (MAP), heart rate (HR), and postoperative recovery time, dizziness, nausea and vomiting were recorded and compared.Results: From February to July 2022, 193 patients were recruited and randomly assigned to group P (n=64), group R (n=64), or group RP (n=65). There was no significant inter-group difference of the intraoperative BIS values. The incidence of low SpO2, injection pain, hypotension, and postoperative dizziness in group RP were less than that in group P, and had no significant difference from group R. The incidence of body movement in group RP was less than that in group R, and had no significant difference from group P. Postoperative recovery time of group RP was shorter than that of the other two groups. No significant inter-group difference in bradycardia, nausea and vomiting was observed.Conclusion: Remimazolam tosylate combined with low dose of propofol improved sedation and safety in hysteroscopy, and may be a more ideal sedative method for hysteroscopy.Keywords: remimazolam tosylate, propofol, sedation, hysteroscopy